1984
DOI: 10.1111/j.1744-7348.1984.tb03070.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of a combined cold storage and methyl bromide fumigation treatment to control the American serpentine leaf miner Liriomyza trifolii (Diptera:Agromyzidae) in imported chrysanthemum cuttings

Abstract: Individual chrysanthemum cuttings and leaves infested with eggs and larvae of the alien leaf miner Liriomyza trifolii, and batches of pupae, were treated in the laboratory to find an effective quarantine treatment to control the pest in imported cuttings. The laboratory tests were based on a statutory quarantine treatment of 2 days' cold storage at 1-2°C followed by methyl bromide fumigation at 15°C with a concentration time product (CTP) of 54 g h/m3, which is used to control Spodoptera littoralis on imported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

1988
1988
1999
1999

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 5 publications
0
18
0
Order By: Relevance
“…As an example, research on L. trifolii led to the development of in-transit treatments to eradicate this pest from chrysanthemum cuttings before introduction into rooting areas. Mortimer & Powell (1984) proved that a methyl bromide fumigation at 15°C with a CTP of 54 g h m-3 was effective and could be used practically without undue phytotoxiciry. Biological studies proved that natural overwintering in Britain by L. trifolii was highly unlikely (Miller & Isger, P .…”
Section: Researchmentioning
confidence: 97%
“…As an example, research on L. trifolii led to the development of in-transit treatments to eradicate this pest from chrysanthemum cuttings before introduction into rooting areas. Mortimer & Powell (1984) proved that a methyl bromide fumigation at 15°C with a CTP of 54 g h m-3 was effective and could be used practically without undue phytotoxiciry. Biological studies proved that natural overwintering in Britain by L. trifolii was highly unlikely (Miller & Isger, P .…”
Section: Researchmentioning
confidence: 97%
“…As UK growers were dependent on a limited number of suppliers, this had a severe impact on the industry and prompted investigation of further phytosanitary disinfestation treatments. A pretransit treatment combining cold storage and methyl bromide fumigation was developed by Mortimer & Powell (1984), which was later adopted as an internationally recognized fumigation standard (OEPP/EPPO, 1984a) and became a requirement under UK phytosanitary legislation (Anonymous, 1987). This phytosanitary treatment was subsequently used against Lirioniyzn huidobrensis, when outbreaks first occurred in the UK from 1989.…”
Section: Quarantine Treatments For Pest Exclusionmentioning
confidence: 99%
“…A quarantine treatment of 2 days' cold storage at 1-2°C followed by methyl bromide fumigation at 15°C with a concentration time product (CTP) of 54g h/m3 gave almost complete kill of most stages of L. trifolii in chrysanthemum cuttings cv. Yellow Snowdon (Mortimer & Powell, 1984). The first objective of the present investigation was to ensure that this treatment also controls L. trifolii in cultivars of chrysanthemum other than Yellow Snowdon.…”
Section: Culrivar Eflectmentioning
confidence: 99%
“…In commercial practice, if fumigation followed cold storage, it would be difficult to raise the temperature of cuttings enclosed within Polythene wrappers inside boxes from the 1 -2°C cold storage temperature uniformly to 15°C prior to fumigation, without an extensive warming-up period. Studies of the methyl bromide LD99s for eggs, larvae and pupae fumigated at 15°C (Mortimer & Powell, 1984) had indicated that there might be some scope for reducing the fumigation temperature while still obtaining a high degree of kill of L. trifolii. Fumigating at the lowest possible temperature should also minimise the phytotoxic effect of the treatment (Powell, 1979).…”
Section: Fumigation Temperaturementioning
confidence: 99%
See 1 more Smart Citation